Heating Characteristics of Palm Oil Industry Solid Waste and Plastic Waste Mixture using a Microwave Oven - Novi Caroko; Harwin Saptoadi; Tri Agung Rohmat (ASEAN Journal of Chemical Engineering, 2020)
A microwave thermogravimetric analyzer was used to measure the characteristics of a mixture of palm oil solid waste (fiber, shell, and empty fruit bunch) and polyethylene terephthalate (PET). In the study, the range of palm oil solid waste composition ratios to PET used was 100:0, 75:25, 50:50, 25:75, and 0:100 (by weight). The study included the influence of the quality of raw material on the heating process. The mixture of palm oil solid waste (fiber, shell, and empty fruit bunch) and PET proved to impact the heating rate, mass-loss rate, and energy consumption. Based on the observation, empty fruit bunch-PET mixture had the highest heating rate (average 1.5039oC/s) than shell (average 0.6058oC/s), and fiber (0.9119oC/s) and also had the highest mass-loss rate (average 0.0253 g/s). The highest biomass (shell, empty fruit bunch, and fiber) and PET composition ratio give the highest rate of heating rate (average 1.8264oC/s) and mass-loss rate (average 0.02875 g/s). In addition, the increasing ratio of fixed carbon and material density will impact the increasing heating rate and mass-loss rate and decrease energy consumption. Therefore, fixed carbon and material gaps significantly affect the heating rate.